Evaluating the quality of UCP-based framework using CK metrics - Che Ani, Zhamri; Hashim, Nor Laily; Harun, Hazaruddin; Basri, Shuib; Sarlan, Aliza (The Science and Information (SAI) Organization Limited, 2018)
Software effort estimation is one of the most important concerns in the software industry. It has received much attention since the last 40 years to improve the accuracy of effort estimate at early stages of software development. Due to this reason, many software estimation models have been proposed such as COCOMO, ObjectMetrix, Use Case Points (UCP) and many more. However, some of the estimation methods were not designed for object-oriented technology that actively encourages reuse strategies. Therefore, due to the popularity of UCP model and the evolution of the object-oriented paradigm, a UCP-based framework and supporting program were developed to assist software developers in building good qualities of software effort estimation programs. This paper evaluates the quality of the UCP-based framework using CK Metrics. The results showed that by implementing the UCP-based framework, the quality of the UCP-based program has improved regarding the understandability, testability, maintainability, and reusability.